Caterpillar-like sub-micron LiNi0.5Mn1.5O4 structures with site disorder and excess Mn3+ as high performance cathode material for lithium ion batteries. (10th September 2016) - Haridas, Anulekha K.; Sharma, Chandra S.; Rao, Tata N.
Graphical abstract: Highlights: Electrospun Fd3m nanostructured LNMO caterpillars as high performance cathode. Polymer assisted e-spinning facilitates presence of Mn 3+ in the crystal structure. Specific capacity of 100 mAh g −1 at 5 C rates for nanostructured LNMO caterpillars. Excellent cycle stability with high capacity retention even after 100 cycles. Abstract: Caterpillar-like spinel LiNi0.5 Mn1.5 O4 (LNMO) sub-micron structures with Fd3m space group were synthesised by polymer assisted sol-gel/electrospinning and post heat treatments in air atmosphere. The novel caterpillar structures were composed of 60–100 nm sized well sintered and interconnected nano grains as observed by FESEM and TEM studies. The presence of Fd3m structure in the LNMO caterpillars were confirmed using X-Ray Diffraction and Raman spectroscopy studies. The Cyclic Voltammetry and Galvanostatic charge-discharge studies revealed the presence of substantial amount of Mn 3+ in LNMO caterpillars. The LNMO caterpillar structures have exhibited high rate capability and excellent capacity retention (118 mAh/g at 1 C rate) after 100 cycles of charge discharge, when compared with P43 32 LNMO sol heated powders (82 mAh/g at 1 C rate) synthesised in the absence of polymer. The EIS studies revealed low charge transfer resistances in LNMO caterpillars (4 times lower) in comparison to LNMO sol heated powders. The prepared LNMO caterpillar like structures with considerable Mn 3+ concentration can be considered as a high performance cathode material for Lithium ion batteries.